Faktor Pendukung Kualitas Produk Tempe di Desa Sukawening, Kecamatan Dramaga, Kabupaten Bogor - Neng Rahayu Novita; Zaenal Abidin (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Tempeh is one of Indonesian traditional foods, made from soybean or some other ingredientswhich is processed through fermentation from tempe yeast that have a lot of mold Rhizopus sp.The purpose of this activity is to find out the support factors that influence the quality of tempe inSukawening Site. These factor includes is soybean, process water, yeast, fermentation time andtemperature of fermentation. This activity was conduct by interviewing and visiting house tempeproduction in Sukawening Village. The ingredients for making tempeh is soybean, which is imporsoybean because the size of soybean is big, use process water by groundwater because the cost islow , and use yeast by local yeast bought from market. Fermentation time around two days andtemperate of storage’s tempe process on the roof close to asbestos is around 29,23 0C. Supportingfactors for the quality of tempeh are the ingredients used in the manufacture of tempeh and resupported by proper washing soybean and the use of good of yeast as well as proper curing time.Suggestion for further activities is further quantitative research is conducted on supporting factorsin making tempeh.